Internal Governance and Performance: Evidence From When External Discipline is Weak - Kalodimos,Jonathan (Journal of Corporate Finance, 2017)
The effect of internal governance on performance is potentially economically significant but may be difficult to identify because of confounding external disciplinary mechanisms and the endogenous choice of internal governance. This study addresses those difficulties by using nonprofit hospitals as an economic environment with muted external disciplinary mechanisms and instrumenting for internal governance using governance spillovers of geographically local public firms. Using patient heart attack survival as a measure of performance, a one standard deviation increase in strength of internal governance reduces the probability of death by 0.89 percentage points after controlling for patient characteristics.
Keywords: Finance